Markučiai ― Markucie ― Маркутье: The History of the Names of One Vilnius Area - Sinočkina, Birutė (Slavistica Vilnensis, 2021)
The article deals with the historical Russian toponyms corresponding to the aboriginal Lithuanian Markučiai. In the past, this area has changed a number of names, the historical Russian forms of Маркутье and Маркуци have survived to this day. Based on the data of texts of various genre and stylistic attribution, the functioning of both toponyms can be traced during the 2nd half of the 19th – early 20th centuries.The article is an attempt to identify the factors that determined the duality of the historical Russian name. The study showed that the fate of competing toponyms was influenced not only by the real linguistic situation in the Vilna region, but also by the purposeful russification activity of the authorities after the suppression of the Polish uprising of 1863–1864. The forms of the same type of Belarusian oikonyms, Baltic in origin and ascending to Lithuanian personal names, confirm the non-systemic nature of the Vilna toponym Маркутье.
Keywords: toponyms; oikonyms; anthroponyms; language contact; local language; russification